Genomic Insights of “Candidatus Nitrosocaldaceae” Based on Nine New Metagenome-Assembled Genomes, Including “Candidatus Nitrosothermus” Gen Nov. and Two New Species of “Candidatus Nitrosocaldus” - Luo, Zhen-Hao; Narsing Rao, Manik Prabhu; Chen, Hao; Hua, Zheng-Shuang; Li, Qi; Hedlund, Brian P.; Dong, Zhou-Yan; Liu, Bing-Bing; Guo, Shu-Xian; Shu, Wen-Sheng; Li, Wen-Jun (Frontiers in Microbiology, 2021)
“Candidatus Nitrosocaldaceae” are globally distributed in neutral or slightly alkaline hot springs and geothermally heated soils. Despite their essential role in the nitrogen cycle in high-temperature ecosystems, they remain poorly understood because they have never been isolated in pure culture, and very few genomes are available. In the present study, a metagenomics approach was employed to obtain “Ca. Nitrosocaldaceae” metagenomic-assembled genomes (MAGs) from hot spring samples collected from India and China. Phylogenomic analysis placed these MAGs within “Ca. Nitrosocaldaceae.” Average nucleotide identity and average amino acid identity analysis suggested the new MAGs represent two novel species of “Candidatus Nitrosocaldus” and a novel genus, herein proposed as “Candidatus Nitrosothermus.” Key genes responsible for chemolithotrophic ammonia oxidation and a thaumarchaeal 3HP/4HB cycle were detected in all MAGs. Furthermore, genes coding for urea degradation were only present in “Ca. Nitrosocaldus,” while biosynthesis of the vitamins, biotin, cobalamin, and riboflavin were detected in almost all MAGs. Comparison of “Ca. Nitrosocaldales/Nitrosocaldaceae” with other AOA revealed 526 specific orthogroups. This included genes related to thermal adaptation (cyclic 2,3-diphosphoglycerate, and S-adenosylmethionine decarboxylase), indicating their importance for life at high temperature. In addition, these MAGs acquired genes from members from archaea (Crenarchaeota) and bacteria (Firmicutes), mainly involved in metabolism and stress responses, which might play a role to allow this group to adapt to thermal habitats.